The Accommodation Pattern of Batak Society Language in Trading Domain with Javanese Society in Semarang - Limbong, Alibasa; Zulaeha, Ida (Pascasarjana Universitas Negeri Semarang, 2018)
Batak Society as newcomers or minority in Semarang accommodates its language. One of the domains requiring accommodation is trading. The purpose of this research is to analyze Batak society language accommodation in trading domain to Javanese in Semarang. The research uses sociolinguistics approach as its methodology. The data is collected by using observation and record as the basic techniques. Then it is continued by participant observation, free involved observation, recording, and noting. The data analysis is done using coding method and interactive model. Based on the findings, they show the accommodation pattern are (1) pattern of Javanese  accommodation convergent, (2) pattern of Javanese accommodation most convergent, (3)  pattern of Batak Toba language accommodation  divergent, (4) pattern of Batak Karo language accommodation  divergent, and (5) pattern of Batak Simalungun language accommodation divergent.